Urgency of National Digital Accessibility Standards for Inclusive Online Services (Open Society Conference, 2025)
This study investigated the absence of a clear and binding national standard on digital accessibility in Indonesia, which has created a significant legal gap and hindered equal access to online services for persons with disabilities. Although existing regulations, such as Law Number 8 of 2016 concerning Persons with Disabilities and Law Number 1 of 2024 concerning the Second Amendment to Law Number 11 of 2008 on Electronic Information and Transactions, uphold the principle of non-discrimination, they have not provided technical provisions aligned with international standards such as the Web Content Accessibility Guidelines (WCAG). This research was conducted using a normative juridical approach, supported by statutory analysis and comparative studies with global best practices. The proposed approach emphasized the integration of WCAG-based technical requirements into Indonesian legal frameworks, either through ministerial regulations or the development of a dedicated Indonesian National Standard (SNI). The findings revealed that the absence of such a legal framework leads to inconsistent implementation between government and private digital platforms, causing structural digital exclusion. The study concluded that regulatory reform is urgently needed to ensure inclusive and standardized digital environments. This reform would not only harmonize national practices with global norms but also strengthen Indonesia’s commitment to the United Nations Convention on the Rights of Persons with Disabilities (CRPD), enhance social participation, and expand economic opportunities for persons with disabilities.